Reproductive traits in four spontaneous Pappophorum vaginatum populations in arid Argentina - Entío, L. (2021)
Arid zones, where native rangelands are common, are essentials for millions of people livelihood. These areas support 50% of the world’s livestock and are where 44% of the world’s food is grown. In rangelands of Central Argentina, Pappophorum vaginatum is basically the unique, warm-season perennial grass species palatable to grazing livestock. Our major objective was to determine variability in reproductive characteristics among four spontaneous, overgrazed populations (i.e., P1, P2, P3, P4) of that species to identify promissory materials for domestication. Studies were conducted during three consecutive growing seasons within the southwestern part of the Phytogeographical Province of the Monte, in southwestern Buenos Aires, Argentina. Measured reproductive characteristics were related to flowering initiation, seed production and natural reseeding potential. Significant differences were found for flowering initiation and natural reseeding potential, but not for viable anthecia per plant among the four populations of P. vaginatum. This species fructified from the beginning to the end of the studied growing seasons with a great anthecia production per plant. The light weight of these anthecia and their awns would favor a great wind dispersal and most likely the establishment of new seedlings of P. vaginatum. This suggests that sexual reproduction might have a relatively greater importance than asexual reproduction (i.e., tillering) in the persistence of the overgrazed P. vaginatum in the plant communities of the studied region. Se-lection of plant materials with a late flowering initiation will allow to extend the forage production of a better quality. The variability among and within populations found on this study support the idea that would be promissory to start selection programs to obtain improved germplasm to reincorporate to grasslands of the south of the Phytogeographical Region of the Monte (Argentina) not only to increase livestock production but to recover and maintain biodiversity.